2004
DOI: 10.1074/jbc.m209733200
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin-resistant Proliferation of CD8+ T Cells Correlates with p27 Down-regulation and bcl-xL Induction, and Is Prevented by an Inhibitor of Phosphoinositide 3-Kinase Activity

Abstract: Rapamycin inhibits the proliferation of many mammalian cell types, including lymphocytes, making the compound useful as an immunosuppressant. Rapamycin has also been a useful tool for studying signaling mechanisms regulating cellular proliferation. However, the effects of rapamycin remain poorly understood, and the precise mechanisms of clinical action remain elusive. Previously, we found that, depending on the strength of the signal delivered to the T cell via both the T cell receptor and the costimulatory mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 50 publications
5
39
1
Order By: Relevance
“…Our finding that rapamycin-generated Th2 cells manifest a broad apoptosis-resistant phenotype may not have been predicted from the numerous studies that associate mTOR inhibition with increased T cell apoptosis (49 -53), but is consistent with knowledge that rapamycin-resistant human CD8 ϩ T cells have an increase of antiapoptotic Bcl-x L (24) and that rapamycin resistance in murine T cells is mediated through the Pim-1 and Pim-2 kinases that confer antiapoptotic, growth, and proliferative effects (44,45). The Th2.R cells used in our study were rapamycin resistant, as they expanded in high-dose rapamycin in the setting of reduced phosphorylation of molecules dependent upon mTOR kinase activity, 4EBP1 and S6 ribosomal protein.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our finding that rapamycin-generated Th2 cells manifest a broad apoptosis-resistant phenotype may not have been predicted from the numerous studies that associate mTOR inhibition with increased T cell apoptosis (49 -53), but is consistent with knowledge that rapamycin-resistant human CD8 ϩ T cells have an increase of antiapoptotic Bcl-x L (24) and that rapamycin resistance in murine T cells is mediated through the Pim-1 and Pim-2 kinases that confer antiapoptotic, growth, and proliferative effects (44,45). The Th2.R cells used in our study were rapamycin resistant, as they expanded in high-dose rapamycin in the setting of reduced phosphorylation of molecules dependent upon mTOR kinase activity, 4EBP1 and S6 ribosomal protein.…”
Section: Discussionsupporting
confidence: 73%
“…Relative to control Th2 cells, we found that Th2.R cells expressed similar levels of Pim-1 (six of six cases) and Pim-2 (six of six cases). As a third possibility, we evaluated Th2.R cell expression of the cell cycle inhibitor p27, which is down-regulated in rapamycin-resistant human CD8 ϩ T cells (24). Consistent with this previous observation, we found that Th2.R cells had reduced expression of p27 in six of six cases.…”
Section: Th2 Cell Rapamycin Resistance: Evaluation Of Potential Mechasupporting
confidence: 70%
See 2 more Smart Citations
“…In particular, one tyrosine (Y170 in mouse CD28, Y173 in human CD28) that is important in PI3K activation permits CD28 to recruit SH2-containing signaling molecules, including PI3K, Grb2, and Gads that control the regulation of bcl-xL (21,74). However, whether or not this regulation was dependent on mammalian target of rapamycin pathway is still controversial (13,75). CD28 also promotes expression of bcl-2, bfl-1 (A1), and myeloid cell leukemia sequence 1 (mcl-1) to regulate T cell survival (76)(77)(78).…”
Section: Cell Survivalmentioning
confidence: 99%